Spontaneous vegetative propagules differentiation in Bowdichia virgilioides seedlings maintained at MS basal medium - Boaventura Filho, Marco Aurélio; Leite, Marco Aurélio; Mc Leod, Lelia; Régis Santos, Breno; Rodrigues dos Santos Filho, Plinio (Revista Ceres, 2025)
Bowdichia virgilioides Kunth is a medium size tree used in folk medicine and in furniture manufacturing which makes it a target of extractive processes. The aim of this work was to evaluate the endogenous content of polymines, amino acids, and sugars in seedlings of Bowdichia virgilioides that presented or not the development of spontaneously differentiated vegetative propagules in their roots. An average of thirty percent Bowdichia virgilioides in vitro growing plants cultivated in MS basal medium without growth regulators presented the differentiation of vegetative propagules. It was noted the propagules units presents embryo-like structures (globular - to leaf-shaped features) and these plants showed a compromised development when compared to the plants that do not presented these morphogenetic structures. Total sugars and amino acids content was significantly higher in the roots of plants with the vegetative propagules. With regard to polyamines content, there was no statistical difference, for spermine and spermidine. However, higher levels of putrescine were found in plants developing vegetative propagules. In this way, these results showed that this event are related to the amino acids, sugars and polyamines, mainly putrescine content.